The Accuracy of Yoon’s Formula for Predicting Central Venous Catheter Depth in Indonesian Pediatric CHD Patients: A Cross Sectional Study - Meidisa Akhmad, Adinda; Soenarto, Ratna Farida; Heriwardito, Aldy; Nathania, Eloisa (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif (PERDATIN) / The Indonesian Society of Anesthesiology and Intensive Care (INSAIC), 2025)
Introduction: A central venous catheter is a routinely inserted tool by anesthesiologists in open-heart surgery. However, incorrect central venous catheter placement depth may lead to complications or suboptimal usage. Yoon’s research in 2006 was done in paediatrics with congenital heart disease in Asia and developed a prediction formula for the depth of central venous catheter. This study aims to prove if Yoon’s formula can be applied to pediatric patients with congenital heart disease in Indonesia. Methods: This analytic observational study, with a cross-sectional design, involved 38 patients undergoing open-heart surgery in RSCM. Yoon’s formula determines the depth of central venous catheter placement. Transesophageal echocardiography assessed the position of the tip of the central venous catheter from the cavoatrial junction to confirm the depth’s accuracy. Results: Yoon’s formula can predict the optimal depth of the central vein catheter 63.16% of the time. There was no complication before central venous catheter placement. This study is limited to right internal jugular vein placements, reducing its generalizability to other insertion sites. Further research with a larger sample and varied approaches is needed to enhance accuracy and develop a more suitable formula. Conclusion: Yoon’s formula is inappropriate for predicting the depth of central vein catheters in pediatric patients with congenital heart disease in Indonesia, but it can still be applied clinically.